Generation of phase-only holograms with high-diffraction-order reconstruction by a U-Net-based neural network: A phase grating perspective - Liu, Xinlei; Yan, Xingpeng; Wang, Xi; Jing, Tao; Li, Pei; Song, Cheng; Qu, Qiang; Jiang, Xiaoyu (Frontiers in Physics, 2022)
Implicit periodic structure in phase-only holograms will result in many diffraction orders in the diffraction field. We analyzed the diffraction pattern from a phase grating’s point of view, and proved that the diffraction orders were jointly influenced by the phase factor, the single-beam diffraction factor and the multi-beam interference factor. According to the analysis, we proposed the high-diffraction-orders angular spectrum method (HDO-ASM) for the numerical reconstruction of high diffraction orders. Different from the conventional methods of removing high diffraction orders, we chose to reconstruct target images in high diffraction orders with HDO-ASM and a U-Net-based neural network. Finally, the 4K phase-only holograms with high-diffraction-orders reconstruction have been generated in 0.09s, which have a mean reconstruction quality of 34.3dB (PSNR) in the DIV2K valid dataset. Theoretical and experimental results demonstrated that there are few speckle noises and fringes in the reconstructed images of holograms generated by the proposed method.